Preschool Wheezing and Gastro-Esophageal Reflux: --Causal or Casual Coincidence? Update from Literature - Borrelli, Melissa (Children (Basel), 2021)
Gastroesophageal reflux (GER) and wheeze are two common conditions in children. GER has been advocated as a causative factor for explaining recurrent to persistent respiratory symptoms at any age. This association very often means that many children with cough, wheezing, or recurrent respiratory infections receive empirical anti-reflux medications. The causal relationship is still largely discussed. Compared to the large number of studies in infants and adolescents, literature on the relationship between GER and wheeze in preschool children is scarce and inconclusive. The aim of the present narrative review was to summarize what is known so far, and what the literature has proposed in the last 20 years, on the relationship between preschool wheezing and GER. In preschool children with respiratory symptoms there is a high rate of positivity of reflux testing, for this reason pH-MII testing and endoscopy are recommended. Flexible bronchoscopy may be useful to exclude anatomical abnormalities as the cause of wheezing in infancy and preschool years. Several biomarkers, as well as empirical anti-reflux therapy, have been proposed for the diagnosis of GER-related airway diseases, but the conclusions of these studies are controversial or even conflicting. There is a great need for future clinical trials to confirm or rule out the association.